Review: The Languages of Early Medieval Charters. Latin, Germanic Vernaculars, and the Written Word. By Robert Gallagher, Edward Roberts & Francesca Tinti (eds.). Brill, 2021. Pp. 548, xvi. - Zagórska, Paulina (Studia Anglica Posnaniensia, 2021)
Review: The Languages of Early Medieval Charters. Latin, Germanic Vernaculars, and the Written Word. By Robert Gallagher, Edward Roberts & Francesca Tinti (eds.). Brill, 2021. Pp. 548, xvi.